2019
DOI: 10.1111/joa.12980
|View full text |Cite
|
Sign up to set email alerts
|

Femoral morphology of sciuromorph rodents in light of scaling and locomotor ecology

Abstract: Sciuromorph rodents are a monophyletic group comprising about 300 species with a body mass range spanning three orders of magnitude and various locomotor behaviors that we categorized into arboreal, fossorial and aerial. The purpose of this study was to investigate how the interplay of locomotor ecology and body mass affects the morphology of the sciuromorph locomotor apparatus. The most proximal skeletal element of the hind limb, i.e. the femur, was selected, because it was shown to reflect a functional signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 26 publications
(67 citation statements)
references
References 92 publications
3
64
0
Order By: Relevance
“…This might indicate that forces acting in any direction increase disproportionately with increasing body mass, necessitating adjustments in the femoral CSP. Furthermore, as Wölfer et al () found isometric scaling for the size of the femoral head in Sciuromorpha, we assume that apposition of compact bone within but not outside of the femoral head is playing a major role in increasing robustness in this region. Concordantly, Mielke et al () discovered positive allometry in the proportion of trabecular volume of overall bone volume in the femoral head in Sciuromorpha.…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…This might indicate that forces acting in any direction increase disproportionately with increasing body mass, necessitating adjustments in the femoral CSP. Furthermore, as Wölfer et al () found isometric scaling for the size of the femoral head in Sciuromorpha, we assume that apposition of compact bone within but not outside of the femoral head is playing a major role in increasing robustness in this region. Concordantly, Mielke et al () discovered positive allometry in the proportion of trabecular volume of overall bone volume in the femoral head in Sciuromorpha.…”
Section: Discussionmentioning
confidence: 68%
“…It should be noted that at approximately 20% femoral length, cross‐sections already represent the diaphysis instead of these two trochanters in some larger aerial species as the one displayed in Figure . This can be explained by the femoral length scaling with 0.39 in relation to body mass in the aerial group, whereas the distances of the third and lesser trochanters from the center of the femoral head (i.e., the in‐levers of the attaching muscles) only scale with 0.35 and 0.36, respectively (Wölfer et al, ). In comparison, all three variables scale with 0.36 in the arboreal group, whereas the lesser trochanter is located even more distal along the midshaft in the fossorial group (its distance scales with 0.36, the femoral length and the distance of the third trochanter with 0.29 and 0.30, respectively; Wölfer et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations